Effect of lorecivivint on osteoarthritis: A systematic review and meta-analysis - Haiyang Kou; Zhong Qing; Guanghui Zhao; Xiangxiang Sun; Liqiang Zhi; Jianpeng Wang; Xinlin Chen; Hao Guo; Rui Zhang; Jianbing Ma (Heliyon, 2023)
Objective: To comprehensively evaluate the effectiveness and safety of lorecivivint inhibitors in the treatment of osteoarthritis through meta-analysis. Methods: A comprehensive literature search on lorecivivint inhibitors in osteoarthritis was performed using electronic databases such as PubMed, Embase, Web of Science, and CochraneLibrary up to July 30, 2022. Two reviewers independently screened, evaluated, and reviewed the eligible studies. Data analysis and processing were carried out using RevMan 5.4 software. Results: A total of six studies involving 3056 participants were included. Meta-analysis showed that compared with the control group, lorecivivint significantly increased WOMAC discomfort (0.03 mg Week 12) (MD = −0.21, 95% CI [-1.94 – 1.53]; P = 0.81), WOMAC function (0.07 mg Week 24) (MD = −1.81, 95% CI [-4.74 – 1.12]; P = 0.23) and Joint space width (0.23 mg Week 24) (MD = −1.16, 95% CI [-3.69 – 1.38]; P = 0.37). Conclusion: A new treatment method combining Wnt pathway modulators with intra-articular CLK2/DYRK1A inhibitors could be a promising therapy for treating osteoarthritis. Lorecivivint was found to significantly improve WOMAC discomfort, WOMAC function, and joint space width in osteoarthritis patients. It is anticipated to be a reliable, safe, and effective treatment option for osteoarthritis with significant therapeutic utility and potential applications.